Plan de negocios para una empresa productora y comercializadora de estribos de construcción civil. - Ruiz Mesías, Gonzalo Daniel (2020)
This project was aimed at developing a business plan for a company that produces and markets stirrups civil construction, focused primarily on mitigating the problem of handling inadequate structural material intermediate in the process of building homes and buildings. Starting from the conceptualization of the business model, ideas were generated that enabled the large-scale industrialization of a product with a value proposition that complies with national and international regulations. The methodology based on the application of a feasibility project structure and using exploratory research, data were mined on the level of consumption of materials for civil construction at the national level; with the collected data, calculations were made on the demand projection, a key point for the formulation of different market, administrative and operational strategies. Additionally, using tools and indicators for economic and financial validation, it was determined that the project enjoys an optimal feasibility margin due to the low ratio of production costs versus the sale price to the public. By submitting the values to a sensitivity and risk analysis, the scenarios confirmed that the start-up of this company is viable given the low competition in the country. Thus, concluding that the Ecuadorian business environment opens doors to the entry of innovative elements within the construction sector as it is an economic activity in constant growth and that brings great movement to the national productive matrix.